Comparison of Post-operative Drain Insertion versus No Drain after Total Thyroidectomy (Medical Forum Monthly, 2024)
Objective: To compare insertion of post-operative drain versus no drain in patients undergoing total thyroidectomy in terms of operative time, hospital stay and frequency of post-operative complications. Study Design: Randomized controlled trial. Place and Duration of Study: This study was conducted at the Department of General Surgery, Central Park Teaching Hospital, Lahore from 1st July 2016 to 30th June 2017. Materials and Methods: Sixty two patients of benign multinodular goiterwere included in the study. Patients were randomly divided into two equal groups of 31 patients each by lottery method. In Group A, a redivac suction drain was inserted after total thyroidectomy while Group B post-operative drain was not placed. Mean operative time, hospital stay and postoperative complications between the two groups were compared. Results: The mean operation time was 73.16±10.15 minutes in Group A while it was 61.23±8.61 minutes in Group B(p=0.000). The mean hospital stay was 2.42±0.50 days in Group A while it was 1.44±0.53 days in Group B(p=0.000).The mean pain score in Group A was 4.77±0.99 while in Group B it was 3.23±1.12(p=0.000). The difference in complications (hematoma, seroma and surgical site infection) was non-significant (p=0.641). Conclusion: Total thyroidectomy for benign multinodular goiter without post-operative drains had a less operative time, lesser hospital stay and was associated with less post-operative pain as compared to patients with postoperative drain insertion. The complication rate between the two groups was comparable.